Yield loss assessment in common bean due to anthracnose (Colletotrichum lindemuthianum) under sub temperate conditions of North-Western Himalayas - B.A. PADDER and R. KAPIL, P.N. SHARMA*, O.P. SHARMA, (Indian Phytopathology, 2008)
Investigation on yield loss assessment in common bean due to anthracnose (Colletotrichum lindemuthianum) was conducted under field conditions using different cultivars having variable resistance (Baspa, resistant; Him-1, moderately resistant; Local, susceptible; Jawala, highly susceptible). Field experiments revealed maximum disease in terms of incidence and severity on highly susceptible cultivar Jawala under both the situations of infection (seed borne infection and background contamination). The disease drastically affected the growth parameters and yield components in cultivar Jawala causing significant reduction in yield of both the crops raised from infected seed (75%) and under background contamination (57.24%). Seed borne infection caused more yield losses than background contamination. The pod infection had direct effect on seed yield as severity on pods ranging from 3-9 (0-(scale) caused 10.52-57.76 per cent reduction in number of seeds per pod and 21.93-68.77 per cent reduction in seed weight per pod. However, the determinate cultivars showed more reduction in yield as compared to indeterminate type, though both were susceptible.